Optimization of Palm Kernel Cake Bioconversion with P. ostreatus: An Efficient Lignocellulosic Biomass Value-Adding Process for Ruminant Feed - Aldo Ibarra-Rondón; Dinary Eloisa Durán-Sequeda; Andrea Carolina Castro-Pacheco; Pedro Fragoso-Castilla; Rolando Barahona-Rosales; José Edwin Mojica-Rodríguez (Fermentation)
This study aims to optimize the bioconversion of palm kernel cake (PKC) by Pleurotus ostreatus to improve fungal biomass production, lignocellulolytic enzyme expression, and the nutritional value of the substrate as ruminant feed. Three inorganic nitrogen sources (ammonium sulfate, ammonium nitrate, and urea) were evaluated for fungal biomass production using a central composite design (CCD) in liquid fermentations. The formulated culture medium (18.72 g/L glucose and 0.39 g/L urea) effectively yielded better fungal biomass production (8 g/L). Based on these results, an extreme vertex design, mixtures with oil palm by-products (PK, hull, and fiber) supplemented with urea, were formulated, finding that PKC stimulated the highest biomass production and laccase enzyme activity in P. ostreatus. The transcriptome of P. ostreatus was obtained, and the chemical composition of the fermented PKC was determined. Transcriptomic analysis revealed the frequency of five key domains with carbohydrate-activated enzyme (CAZy) function: GH3, GH18, CBM1, AA1, and AA5, with activities on lignocellulose. In the fermented PKC, lignin was reduced by 46.9%, and protein was increased by 69.8%. In conclusion, these results show that urea is efficient in the bioconversion of PKC with P. ostreatus as a supplement for ruminants.